Epidemiology and Antimicrobial Susceptibility of Salmonella enterica Bloodstream Isolates Among Febrile Children in a Rural District in Northeastern Tanzania: A Cross-sectional Study. (7th March 2019) - Msemo, Omari A; Mbwana, Joyce; Mahende, Coline; Malabeja, Anangisye; Gesase, Samwel; Crump, John A; Dekker, Denise; Lusingu, John P A
Abstract: Background: Salmonella enterica including Salmonella Typhi and nontyphoidal Salmonella (NTS) are the predominant cause of community-acquired bloodstream infections in sub-Saharan Africa (sSA). Multiple-drug resistance and emerging fluoroquinolone resistance are of concern. Data on the age distribution of typhoid fever in sSA are scarce but essential for typhoid conjugate vaccine policy. We sought to describe Salmonella bloodstream infections, antimicrobial resistance, and age distribution at a rural district hospital in northeastern Tanzania. Methods: From 2008 to 2016, febrile children or children with a history of fever aged 1 month to 5 years admitted to Korogwe District Hospital were enrolled. Demographic, clinical data and blood cultures were collected. Organisms were identified by conventional microbiological methods, and antimicrobial susceptibility test was done by disc diffusion. Results: Of 4176 participants receiving blood cultures, 383 (9.2 %) yielded pathogens. Of pathogens, 171 (44.6%) were Salmonella enterica of which 129 (75.4%) were Salmonella Typhi, and 42 (24.6%) were NTS. The median (interquartile range age of participants was 13.1 (6.3–28.0) months for those with Salmonella Typhi and 11.5 (8.5–23.4) months for NTS. Of 129 Salmonella Typhi, 89 (89.9%) were resistant to amoxicillin, 85 (81.0%) to chloramphenicol, and 93 (92.1%) to trimethoprim-sulfamethoxazole compared with 22 (62.9%), 15 (39.4%), and 27 (79.4%), respectively, for NTS. Multidrug resistance was present in 68 (81.0%) of Salmonella Typhi and 12 (41.4%) of NTS. Conclusion: Salmonella Typhi was the leading cause of bloodstream infection among infants and young children <2 years of age admitted to Korogwe District Hospital. Multidrug resistance was common, highlighting a role for typhoid conjugate vaccine into routine infant vaccine schedules.